The Evidentiary Value of the Final Discharge of the Worker’s Entitlements under the Saudi Labor Law - Jumana Khalid Ahmed Al-Ghamdi (International Journal of Law Research and Studies, 2025)
This research examines and analyzes the evidentiary value of the final discharge of the worker’s entitlements under the Saudi Labor Law, considering the practical challenges posed by this document at the termination of the employment relationship. The study focuses on highlighting the tension between the evidentiary weight attributed to the discharge on one hand, and the protective nature of the Labor Law on the other, revealing points of conflict between the binding power of the signed discharge and the distinctive nature of labor relations that require special safeguards to protect the worker’s rights.The research has aimed to establish the theoretical foundations of both release and settlement, and to explain the distinctions between them, as this differentiation significantly impacts the legal characterization of labor discharges and the stance of the law toward them. The study also explored the nature of labor rights, their categories, and the permissible boundaries for waiving such rights under the law, illustrating practical applications of these waivers whether at the time of contract formation, during the employment relationship, or upon its termination.Throughout the analysis, the study identified several judicial practices that grant the discharge conclusive evidentiary weight without verifying the actual fulfillment of its content, which undermines the intended protection afforded to the worker. The study further addressed the ambiguity in interpreting Article 8 of the Labor Law, which links the validity of waivers to the realization of the worker’s interest, yet lacks clear standards for assessing this benefit.The research concludes with a set of findings that respond to its research questions, along with practical recommendations aimed at strengthening worker protection and achieving the necessary balance between the stability of labor relations and the safeguarding of workers’ statutory rights.
Keywords: Final Discharge; Release and Settlement in Labor Law; Waiver of Labor Rights; Settlement of Worker’s Entitlements; Evidentiary Value in Labor Disputes; Protection of Worker’s Rights